Innovative Change Strategies for Excellence in Islamic Education: Insights from Indonesia and Thailand - Muhammad Thoyib; Badru Ngoh; Badrudin Badrudin; Linda Ayu Karisma (Jurnal Pendidikan Islam, 2024)
This article delves into the pivotal role of institutional management in facilitating changes crucial for the advancement of Islamic educational institutions amidst escalating global competition. The purpose of the study is to examine how Indonesian Islamic High School IIHS in Indonesia and Bamrung Muslimin High School (BMHS) in Thailand transformed into internationally renowned centers of excellence. Employing a multi-site qualitative approach involving in-depth interviews, observation, and documentation, the study utilizes Miles, Huberman, and Saldana's interactive analytical method. The research underscores three pivotal stages of change management—selection, trajectory, and implementation—that significantly enhance the schools' competitiveness in terms of student performance, faculty, curriculum, and overall quality. The study highlights the imperative of adeptly managing change as a linchpin for these institutions' innovative adaptation, thereby bolstering their capacity to navigate the evolving landscape of national and global educational competition. Ultimately, this study underscores the critical importance of strategic change management in fostering innovation and competitiveness within Islamic education, offering insights into navigating contemporary challenges.